2012
DOI: 10.4102/ojvr.v79i2.457
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation into the introduction and factors for spread of Peste des Petits Ruminants, southern Tanzania

Abstract: A study was carried out to confirm and identify sources and elucidate factors associated with the introduction of Peste des Petits Ruminants (PPR) in southern Tanzania. This study was conducted in Tandahimba and Newala districts of Mtwara region following suspected outbreak of PPR in the area. Qualitative data were collected using semi-structured questionnaires and in-depth interviews of key informants who included goat and sheep owners with suspected cases of PPR and animal health service providers as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 20 publications
6
44
1
Order By: Relevance
“…This follows the official confirmation of PPR in neighboring Kenya in 2007 [7]. The possible spread from Kenya to Tanzania may have been due to the difficulty in controlling transnational livestock movements across borders, especially where Maasai pastoralists are found on either side [12]. In 2011, an outbreak of PPR was reported in southern Tanzania [13].…”
Section: Introductionsupporting
confidence: 61%
“…This follows the official confirmation of PPR in neighboring Kenya in 2007 [7]. The possible spread from Kenya to Tanzania may have been due to the difficulty in controlling transnational livestock movements across borders, especially where Maasai pastoralists are found on either side [12]. In 2011, an outbreak of PPR was reported in southern Tanzania [13].…”
Section: Introductionsupporting
confidence: 61%
“…Poor nutrition due to deficiency of fodder during that period (Wosu et al, 1994) also contributed to the findings. Other workers also established that PPR epidemics tend to occur during the rainy season when goats are herded together and around Christmas when movement to markets increases (Nawathe, 1984;Muse et al, 2012;Salih et al, 2014). The highest outbreaks of PPR occurred in 2011, followed by 2012 and 2010 (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies in northern Tanzania found an overall seroprevalence of 45.5% in 2008 [46] and 22.1% in 2008–2009 [21]. In southern Tanzania, in the Mtwara region bordering Mozambique, 31% of sampled small ruminants had antibodies to PPRV [47]. A recent study analysing samples from 14 different regions of Tanzania described an overall seroprevalence of 27.1%, with regions varying from 2.4% (Kagera) to 72.8% (Morogoro), demonstrating the varying level of seroprevalence within the country [23].…”
Section: Discussionmentioning
confidence: 99%